Methanol crossover reduction by Nafion modification via layer-by-layer self-assembly techniques - Jiang, San ping; Tang, Haolin (Elsevier BV, 2012)
Layer-by-layer (LbL) self-assembly of polyelectrolyte bilayers on the methanol permeability and proton conductivity of Nafion membranes is investigated using polycations PDDA (poly(diallyldimethylammonium chloride)) and PAH (poly(allylamine hydrochloride)) and polyanions PAMP (poly(2-acrylamido-2-methyl-1-propanesulfonic acid)), PAZO (poly(1-(4-(3-carboxy-4-hydroxyphenylazo) benzene sulfonamido)-1,2-ethanediyl, sodium salt)), PSS (poly(sodium styrene sulfonate)) and PAA (poly(acrylic acid)). The formation of polyelectrolyte multilayers on Nafion membranes is confirmed by AFM and UV–visible spectroscopy. The lowest methanol permeability is observed on the self-assembled PDDA-PAA and PAH-PAA bilayers with the exponential growth process. The observed exponential growth process of polyelectrolyte multilayers with PAA polyanion is most likely related to small monomeric block of PAA, resulting in low steric hindrance and high flexibility and mobility of the ionomers and thus promoting the interdiffusion of PAA during the self-assembly. PDDA polycation shows a much better ability to block methanol crossover in comparison with that of PAH polycation. This study shows the importance of LbL self-assembled multilayer structure on the proton conductivity and methanol crossover properties of modified Nafion membranes for application in direct methanol fuel cells (DMFCs).